Implant-Based Breast Reconstruction Outcomes Using Oxychlorosene for Pocket Irrigation. Issue 3 (September 2021) - Dawson, Steven E.; Bamba, Ravinder; Tran, Phu C.; Mailey, Brian; Lin, Jenny; Lester, Mary; Sinha, Mithun; Hassanein, Aladdin H.
Abstract : Supplemental Digital Content is available in the text.